Acne vulgaris and quality of life among young adults in South India - Priya Cinna T Durai; Dhanya G Nair (Wolters Kluwer Medknow Publications, 2015)
Acne vulgaris is a chronic condition affecting more than 85% of adolescents and young adults. It is one of the most common diseases affecting humanity and its impact on quality of life (QoL) is important. The impact of acne on QoL in Indian patients remains undocumented. The study was undertaken to detect the impact of acne vulgaris and related factors that may influence the QoL. Materials and Methods: This was a hospital-based, prospective, cross-sectional, prestructured, questionnaire-based study done on 140 consenting individuals, who attended the Dermatology outpatient department. Acne vulgaris was graded using simple grading system. QoL was measured using a combination of skin disease-specific (Dermatological Life Quality Index (DLQI)) and acne-specific (Cardiff Acne Disability Index (CADI)) questionnaires. Results: Majority of our study population were students (103, 73.6%). Face (139, 99.3%) was the commonest site of acne and comedones 133, 95% were the commonest type of lesion. Most of the individuals 66, 47.1% were observed to have grade 1 acne. The mean DLQI score was 6.91 and the mean CADI score was 5.2. Association between the scores was statistically significant. Age, occupation, marital status, family, and treatment history played a role in affecting the QoL. Diet, smoking, and alcohol did not influence the QoL . Conclusion: Though acne had impact on patient's QoL, it was less severe in our study. It is important for health professionals to incorporate QoL measurements when managing acne patients to provide better and appropriate care.